Social regeneration through physical facilities provided to the vulnerable and disadvantaged groups - Mohamed Osman, Mariana; Bachok, Syahriah; M Bakri, Nurul Izzati (Elsevier, 2015)
Social equality incorporates the concept of social sustainability in urban regeneration process into its definition. Taking cognizance of the importance of barrier free environment towards social equality and equal opportunity for all, especially to the disabled and vulnerable groups within the society, has been an active gesture in the urban regeneration process. Therefore, this research is to analyse current facilities provided for vulnerable and disadvantaged group as part of achieving social sustainability through inclusive environment. The findings from this research obtained from on-site observation and interview and aims to improve the government delivery system in Perak, a state in Malaysia